Resuscitating 'the Forgotten Sector in a Forgotten State': Catalyzing Improved Health Outcomes in Guinea-Bissau through the Millennium Development Goals - Murphy, Stephen (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The citizens of Guinea-Bissau suffer among the worst health indicators in the world. Poor health, education, and economic development in the country stem from weak governance and insufficient and volatile aid flows. At the dawn of the twenty-first century, Guinea-Bissau has joined other low-income countries in embracing the Millennium Development Goals (MDGs). The Ministry of Public Health in Guinea-Bissau seeks to reform health care through an emphasis on the MDGs. The individual MDGs provide concrete health targets, and the government's commitment to their collective pursuit has inspired reinvigorated planning and coordination. Given the strong role of improved health outcomes in fostering poverty reduction, Guinea-Bissau's achievement of the health-related MDGs could have spill-over effects far beyond the health sector. With technical assistance from the World Bank and the United Nations, the Ministry of Public Health is leading a campaign to deliver high-quality, affordable care through improvements in health infrastructure, human resources, and health financing. Instituting user-fee and cost-recovery reforms remain its top priorities. Reforms beyond the health sector related to agriculture, infrastructure, education, and water and sanitation can also contribute substantially to the health-related MDGs. With effective governmental stewardship across ministries and adequate assistance from international partners, the Ministry of Public Health's strategic plan for reform holds the potential to accelerate Guinea-Bissau's achievement of the health-related MDGs. However, renewed political instability or inconsistent donor support could jeopardize progress.